miR-613 inhibits bladder cancer proliferation and migration through targeting SphK1 - Yu, Haifeng (Am J Transl Res, 2017)
Objectives: Increasing evidence has suggested that microRNA (miRNA) dysregulation may contribute to tumor progression and metastasis. However, the role of miR-613 in bladder cancer was still unknown. Materials and methods: qRT-PCR and Western blotting were performed to detect the expression of miR-613 and its direct target gene. CCK-8 analysis, qRT-PCR and cell invasion were performed to measure the cell function. Results: We demonstrated that the expression of miR-613 was downregulated in the bladder cancer cell lines. In addition, miR-613 expression was downregulated in the bladder cancer tissues compared to the adjacent normal tissues. Out of 35 bladder cancer tissues, miR-613 was downregulated in 27 cases compared to the adjacent tissues. Ectopic expression of miR-613 suppressed the bladder cancer cell proliferation and invasion. Moreover, miR-613 overexpression enhanced the expression of epithelial biomarker, Ecadherin, and suppressed the expression of mesenchymal biomarker, Vimentin, Snail and N-cadherin. Furthermore, we identified the Sphingosine kinase 1 (SphK1) as the direct target gene of miR-613 in the bladder cancer cell. Restoration of Sphk1 partially rescued miR-613-inhibited bladder cancer cell proliferation, invasion and EMT. Conclusions: These data suggested that miR-613 acted a tumor suppressive role in bladder cancer through targeting SphK1 in bladder.